Standard vs. mass training in basic life support and defibrillation: a prospective analysis among Italian high school students within a municipal project - Luca Dal Corso; Massimiliano Aldegheri; Elena Anselmi; Alberto Burro; Francesca Moretti; Fabio Rossi; Simone Sebastiani; Davide Silvagni; Michele Zandonà; Maria Angela Cerruto (Emergency Care Journal)
Italian Law No. 116/2021 highlights the necessity of basic life support (BLS) education in schools, especially for secondary school students. This study assessed the efficacy of two basic life support and defibrillation (BLSD) training models — standard teaching method (SE) and mass teaching method (ME) — focusing on student satisfaction and skill retention. Between January 2023 and April 2024, high school students attended either SE sessions (24 students per session) or ME sessions (100 students per session). Both groups completed a 5-hour course following Italian Resuscitation Council Guidelines with an instructor-student ratio of 1:6. Skill retention was assessed immediately and after four months; satisfaction was measured via the Likert scale. Among 1307 students, 899 completed the follow-up. ME students showed superior skill in environmental safety and compression frequency, while SE students excelled in hand placement. Satisfaction levels were high in both groups, with no significant differences, indicating both SE and ME methods were well received.